Dua Dekade Setelah Peristiwa Traumatis: Prevalensi Kesehatan Mental Penyintas Tsunami Aceh - Amna, Zaujatul; Santy, Dini Hari; Nurhasanah, Dini; Aristo, Nayomi; Datachi, Siti Tamita (ANIMA Indonesian Psychological Journal, 2025)
The long-term psychological impact of a traumatic natural disaster, such as the 2004 Aceh Tsunami, is still poorly documented in the scientific literature. The purpose of this study was to describe the mental health status of survivors of the 2004 Aceh Tsunami 20 years after the Aceh Tsunami, utilizing a descriptive quantitative research design. The study participants were 197 tsunami survivors selected by purposive sampling, with specific criteria: (1) being victims directly exposed to the 2004 Aceh Tsunami; and (2) being members of the Aceh community. The Mental Health Inventory-18 (MHI-18; α = .93) was utilized as the data collection instrument for mental health in this study. The results of the data analysis showed that the majority of survivors (78.17%) had low mental health or psychological well-being, reflecting ongoing psychological disorders even though 20 years had passed since the disaster. The findings of this study indicate that the psychological impact of the Aceh Tsunami continues in the long term, significantly affecting psychological well-being. The results of this study emphasize the need for special attention to the mental health of disaster survivors, as well as the importance of long-term support programs to mitigate the long-term psychological impacts post-disasters.